Penggunaan Gen GH sebagai Marka Molekuler DNA Gurami, Osphronemus goramy dalam Pengembangan Teknologi Surrogate Broodstock - Achmad, Marlina; Alimuddin, Alimuddin; Carman, Odang; Arfah, Harton; Zairin, Muhammad (Jurnal Perikanan Universitas Gadjah Mada, 2009)
The technology of fish germ cell transplantation had been established to create broodstock systems by which a target offspring can be produced from a surrogate parent. Donor cell for transplantation is derived from transgenic fish carrying green fluorescent protein gene functions as a marker to distinguish the donor from recipient cell. In this study, an alternative technique was developed for identifying gouramy-derived donor cell and Nile tilapia as recipient by PCR amplification method using growth hormone (GH) gene as a molecular marker.  Specific primer for GH gouramy was designed by using Genetyx version 7 software.  ß-actin gene was used as an internal control of DNA loading. The result showed that a specific PCR amplification product of 340 in length was obtained when the DNA template was from gouramy, while no PCR product from Nile tilapia. The minimum concentration of genomic DNA of gouramy mixed with a 700 ng/µl of Nile tilapia that could be detected by PCR was 1 ng/µl. Thus, PCR method with specific GH primer may be useful to detect the incorporation of donor cell in recipient gonad towards development of surrogate broodstock technology.